Single-Cell Transcriptomics Analysis Showing Functional Heterogeneity in Decidual Stromal Cells during Labor. (April 2021) - Huang, Jingrui; Xie, Yingming; Peng, Qiaozhen; Wang, Weinan; Pei, Chenlin; Zhao, Yanhua; Liu, Rong; Huang, Lihui; Li, Tieping; Nie, Jia; Liu, Lijuan; Zhang, Xiaowen; et al.
To investigate the heterogeneity of decidual stromal cells (DSCs) and their functional alterations during delivery, we conducted single-cell RNA sequencing analysis to characterize the transcriptomic profiles of DSCs before and after labor onset. According to their transcriptomic profiles, DSCs (6382 cells) were clustered into five subgroups with different functions. Similar to stromal cells, cells in cluster 1 were involved in cell substrate adhesion. On the other hand, cells in clusters 2 and 3 were enriched in signal transduction-related genes. Labor onset led to significant alterations in many pathways, including the activator protein 1 pathway (all clusters), as well as in the response to lipopolysaccharide (clusters 1-3). The downregulated genes were involved in coagulation, ATP synthesis, and oxygen homeostasis, possibly reflecting the oxygen and energy balance during delivery. Our findings highlight that peripartum DSCs are heterogeneous and play multiple roles in labor.